2017
DOI: 10.1038/s41598-017-17233-0
|View full text |Cite
|
Sign up to set email alerts
|

Attraction of Halyomorpha halys (Hemiptera: Pentatomidae) haplotypes in North America and Europe to baited traps

Abstract: Halyomorpha halys is a global invasive species, native to Southeast Asia, that is threatening agriculture in invaded regions. Our objectives were to: 1) establish the attractiveness of semiochemical stimuli paired with field-deployed traps in Europe (Greece, Hungary, Italy, and Switzerland), compared with Maryland, USA, and 2) identify H. halys haplotypes recovered from traps at each location. We found qualitatively identical patterns of capture between sites located across Europe and in Maryland, USA. In both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 49 publications
4
40
0
Order By: Relevance
“…Thus, it is plausible that our findings for the Minnesota-acclimated population are most indicative of the H1 haplotype of H. halys. However, additional haplotype analysis with samples from north-central US populations, including Minnesota, are warranted to fully ascertain their genetic identity [50,77,78]. Irrespectively, our results add new information on temperature-dependent longevity and fecundity of H. halys, which is in its early phase of local adaptation and establishment in the MN.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Thus, it is plausible that our findings for the Minnesota-acclimated population are most indicative of the H1 haplotype of H. halys. However, additional haplotype analysis with samples from north-central US populations, including Minnesota, are warranted to fully ascertain their genetic identity [50,77,78]. Irrespectively, our results add new information on temperature-dependent longevity and fecundity of H. halys, which is in its early phase of local adaptation and establishment in the MN.…”
Section: Discussionmentioning
confidence: 67%
“…Most relevant, population(s) of H. halys in the eastern US (samples from NJ, MD, GA, DE, MA, MS, NY, PA, VA, WV, OH, and MI), states that span a distance of 1287-2253 km, are represented by the same Haplotype H1. In the Northwestern US (samples from OR and WA), populations consisted of 4 haplotypes (H1, H3, H23, H47), but had only a single sample of H1, whereas the Korean population consisted of 8 haplotypes (H2, H22, H25, H28, H29, H35, H36, H37), and is strikingly different [50,74,76,77]. Among the eastern US populations studied [74][75][76], OH and MI have the same H1 haplotype, and are geographically closest (< 1126 km) to the MN population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although sticky traps deployed in trees captured significantly fewer H. halys compared with ground-deployed modified pyramid and pipe traps, adult captures in both years and nymphal captures in 2016 were correlated with standard pyramid traps in both apple and peach orchards, suggesting these traps may adequately predict relative H. halys presence, abundance, and seasonal activity, while requiring less effort to enumerate individuals on traps. Moreover, a recent study by Morrison et al (2017a) used clear sticky traps deployed on wooden posts and baited with PHER + MDT to monitor H. halys populations in the eastern United States and in multiple European countries, although how these captures relate to those of standard pyramid traps is unknown. Deploying sticky traps attached atop wooden posts on the ground might reduce the number of structures by which foraging H. halys become arrested on, compared to the numerous and complex branching structures found within tree canopies (as we report here) (Leskey and Nielsen 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Studies on BMSB haplotype diversity in North America and Europe revealed that Italy housed the second most diverse population of the bug, with 2-8 haplotypes represented in Emilia-Romagna, Piemonte and Veneto regions. This suggests that there is an ongoing invasion in Italy, with frequent re-introductions of the bug from several localities [68]. Through the Adige valley passes one of the main traffic corridors (Brennero) linking Italy to the rest of Europe, thus BMSB populations in this valley are thought to be periodically augmented by stratified diffusion via human transportation (i.e., movement of plants, goods and contaminated cargo) from the heavily infested Central Italian regions.…”
Section: Maxent-generated Suitability Mapmentioning
confidence: 99%